2017
DOI: 10.1111/dom.13104
|View full text |Cite
|
Sign up to set email alerts
|

Metformin extended‐release versus immediate‐release: An international, randomized, double‐blind, head‐to‐head trial in pharmacotherapy‐naïve patients with type 2 diabetes

Abstract: This international, randomized, double‐blind trial (NCT01864174) compared the efficacy and safety of metformin extended‐release (XR) and immediate‐release (IR) in patients with type 2 diabetes. After a 4‐week placebo lead‐in, pharmacotherapy‐naïve adults with glycated haemoglobin (HbA1c) at 7.0% to 9.2% were randomized (1:1) to receive once‐daily metformin XR 2000 mg or twice‐daily metformin IR 1000 mg for 24 weeks. The primary endpoint was change in HbA1c after 24 weeks. Secondary endpoints were change in fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 11 publications
0
56
0
2
Order By: Relevance
“…The results showed that metformin XR was non‐inferior to metformin IR for glycaemic control and not superior to metformin IR for overall gastrointestinal adverse events . Another study also showed that metformin XR demonstrated efficacy and safety similar to that of metformin IR . Although there is no good way to completely avoid the gastrointestinal adverse events associated with metformin, starting with a small dose and gradually increasing the dose may be an effective way to reduce side effects of metformin in elderly patients.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that metformin XR was non‐inferior to metformin IR for glycaemic control and not superior to metformin IR for overall gastrointestinal adverse events . Another study also showed that metformin XR demonstrated efficacy and safety similar to that of metformin IR . Although there is no good way to completely avoid the gastrointestinal adverse events associated with metformin, starting with a small dose and gradually increasing the dose may be an effective way to reduce side effects of metformin in elderly patients.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a higher C max is not expected to per se worsen metformin tolerability while maintaining similar pharmacodynamic effect. In a study by Aggarwal et al, 10 metformin extended release resulted in higher C max than metformin immediate release but had better gastrointestinal tolerability at the same total daily dose. Food decreases C max of metformin by 40% and AUC by 25%.…”
Section: Discussionmentioning
confidence: 98%
“…В международном рандомизированном двойном слепом исследовании у 568 лиц с СД 2 типа N. Aggarwal еt al. [72] проводили сравнение эффективности и безопасности метформина XR и метформина IR, продолжительность периода наблюдения составила 24 нед. Метформин XR, имея преимущество дозирования 1 раз в сутки, в целом продемонстрировал равную метформину IR эффективность.…”
Section: A R T I C L E I N P R E S Sunclassified